2007
DOI: 10.1016/j.cell.2007.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Functional Demarcation of Active and Silent Chromatin Domains in Human HOX Loci by Noncoding RNAs

Abstract: Noncoding RNAs (ncRNA) participate in epigenetic regulation but are poorly understood. Here we characterize the transcriptional landscape of the four human HOX loci at five base pair resolution in 11 anatomic sites and identify 231 HOX ncRNAs that extend known transcribed regions by more than 30 kilobases. HOX ncRNAs are spatially expressed along developmental axes and possess unique sequence motifs, and their expression demarcates broad chromosomal domains of differential histone methylation and RNA polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
3,754
6
38

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 3,879 publications
(3,847 citation statements)
references
References 44 publications
49
3,754
6
38
Order By: Relevance
“…[18][19][20] It has been reported that HOTAIR regulates gene expression via epigenetic modifications. 21 For example, Rinn et al demonstrated that HOTAIR interacts with polycomb-repressive complex 2 (PRC2) to increase the trimethylation of histone H3 lysine-27 (H3K27), resulting in the reduction of HOXD gene expression. 21 However, the role of HOTAIR in liver fibrosis has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] It has been reported that HOTAIR regulates gene expression via epigenetic modifications. 21 For example, Rinn et al demonstrated that HOTAIR interacts with polycomb-repressive complex 2 (PRC2) to increase the trimethylation of histone H3 lysine-27 (H3K27), resulting in the reduction of HOXD gene expression. 21 However, the role of HOTAIR in liver fibrosis has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, lncRNA H19 inhibited progression of retinoblastoma cells via offsetting the action of miR‐17‐92 cluster,41 and lncRNA CCAT1 negatively regulated miR‐218‐5p to facilitate the proliferation and growth of SO‐RB50 and Y79 cell lines 13. HOTAIR, situated in chromosome 12 between HOXC11 and HOXC12, covered a length of 2.2 nt,14, 42 so it was also called as long intergenic non‐coding RNA (lincRNA). The lncRNA was equipped with 2 active domains, including 5′‐end that could recruit PRC2, and 3′‐end that combined with lysine specific demethylase (LSD1), RE1‐silencing transcription factor (REST) and REST co‐inhibitory protein (CoREST) 43.…”
Section: Discussionmentioning
confidence: 99%
“…HOTAIR is an OST located at the boundary of two chromatin domains at the HOXC locus (Rinn et al, 2007). Depletion of HOTAIR had no effect on transcription of genes in the HOXC cluster, but did lead to transcriptional activation at the HOXD cluster, which lies on a separate chromosome.…”
Section: How Might Osts Work?mentioning
confidence: 99%